2023
DOI: 10.1177/1098612x231170159
|View full text |Cite
|
Sign up to set email alerts
|

Pyometra alters the redox status and expression of estrogen and progesterone receptors in the uterus of domestic cats

Acácia Eduarda de Jesus Nascimento,
Luciano Cardoso Santos,
Bianca Reis Santos
et al.

Abstract: Objectives The aim of this study was to evaluate the expression profile of sex steroid receptors and redox mediators in the uterus of domestic cats with pyometra. Methods Twelve cats were used and divided into groups: (1) non-gestational healthy diestrus (n = 7) and (2) pyometra (n = 5). The plasma profiles of estradiol and progesterone (P4) as well as uterine expression levels of estradiol alpha (ERα), progesterone (PR) and androgen (AR) receptors, of the antioxidant enzymes superoxide dismutase 1 (SOD1), cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Studies conducted in the last decade with domestic cats have shown that several growth, hormonal, immunological, and redox factors are expressed differently in the uterus and ovary throughout the reproductive cycle [14,[18][19][20][21][22][23][24][25], as well as in the placenta throughout pregnancy [18,19,26,27]. Moreover, these studies show that changes in the expression of some of these factors are involved in the reproductive alterations observed in pyometra [14,[28][29][30] and in feline immunodeficiency virus (FIV) infection [31][32][33][34]. Thus, this paper reviews the current knowledge about the modulation and expression profiles of hormonal, immunological, redox, and growth mediators in the uterus, ovary, and placenta of domestic cats throughout the estrous cycle and during pregnancy.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Studies conducted in the last decade with domestic cats have shown that several growth, hormonal, immunological, and redox factors are expressed differently in the uterus and ovary throughout the reproductive cycle [14,[18][19][20][21][22][23][24][25], as well as in the placenta throughout pregnancy [18,19,26,27]. Moreover, these studies show that changes in the expression of some of these factors are involved in the reproductive alterations observed in pyometra [14,[28][29][30] and in feline immunodeficiency virus (FIV) infection [31][32][33][34]. Thus, this paper reviews the current knowledge about the modulation and expression profiles of hormonal, immunological, redox, and growth mediators in the uterus, ovary, and placenta of domestic cats throughout the estrous cycle and during pregnancy.…”
Section: Introductionmentioning
confidence: 81%
“…In addition, a positive correlation between the genes SOD1 and progesterone (PR) receptor was observed in the uterus of these animals, suggesting that SOD1 expression may be modulated by P 4 . In the subsequent study, de Jesus Nascimento et al [30] showed a trend of increasing the SOD1 gene in uterine samples of cats with pyometra, which showed an increase in P 4 concentration. This study also demonstrated that pyometra reduces the endometrial expression of CAT, positively regulates the gene and protein expression of GPX1, and increases the expression of 8-hydroxyl-2'-deoxyguanosine (8-OhdG), which is an indicator of oxidative DNA damage [179].…”
Section: Uterus and Placentamentioning
confidence: 89%
See 1 more Smart Citation